Pencapaian Performa Pada Katup Variabel Timing Fixed Timing Untuk Mesin Yang Optimal - Ketut Astawa (Department Industrial Engineering, University of Muhammadiyah Malang, 2010)
Problems will be discussed in this research is how differences in exhaust emissions generated by engine with variable valve timing and valve timing on a fixed volume of motor vehicle cylinder 1300 cc. Variable valve timing technology, which is set when opening and closing the intake valve (intake valve) electronic fuel according to engine conditions. This will make mixing air and fuel that enters into an efficient machine that will produce great power, fuel economy and low emissions. Research emissions (CO, CO2, HC, O2) was performedwith dynamic testing, where the vehicle in a state of the load lifted and given transmission. Unlike the testing generally performed with a static test, in which the vehicle is at rest and without a load. This test is performed to determine how the condition of exhaust gases when the vehicle dynamic (analogous to the vehicle running). In general, machines with variable valve timing to produce better emissions than engines with fixed valve timing. The higher the spin machine and load transmission system will result in CO and HC emissions are decreased and O2 and CO2 increased. Engine with variable valve timing control the suction valve opening times to achieve optimum engine performance at various driving conditions. And set out the engineoutput as needed.